The use of traditional knowledge in understanding natural phenomena in the Gulf Province of Papua New Guinea - Pauka, Soikava (Curtin University, 2001)
This study used qualitative (interviews) and quantitative methods (questionnaires) to investigate and describe (a) Papua New Guinea (PNG) village elders' traditional ideas and beliefs on natural phenomena, (b) PNG secondary school student's traditional science beliefs, (c) the sources of PNG secondary school students' explanations of natural phenomena, (d) the types of explanations PNG secondary school students provide to describe natural phenomena, and the views of science teachers and curriculum officers on the inclusion of traditional knowledge in the science curriculum.. Analysis of data included interviews with eight village elders and completed questionnaires from approximately 200 secondary school students in one rural provincial high school in the Gulf Province. Village elders' beliefs were analysed and categorised into (a) spirits, magic spells and sorcery, (b) Christianity, (c) personal experience, and (d) modern science. Secondary school students' sources of explanations were based on what they have heard at (a) home, (b) in the family and village, (c) in church and (d) from school. Approximately half of the secondary school students strongly hold on to traditional beliefs while learning formal school science and these were related to spirits, magic spells and sorcery that were similar to those of the village elders. Students also used scientific explanations of natural phenomena based on their learning in school and from their own personal experiences and interactions with the physical world.Interviews with science teachers and curriculum officers supported the need to include traditional knowledge in the science curricula. The study identified students holding both traditional and scientific explanations of natural phenomena. There is both a need and value for traditional knowledge being incorporated in science education programs that harmonise with school science. The thesis concludes with six recommendations to bring these ideas to fruition.